A Quality systems study of Asian Prime Moulders Inc. - Lerio, Lourberto S. (College of Engineering, 1996)
This report is of the Quality System Study of Asian Prime Moulders Incorporated (APMI).The company is a medium-scale manufacturer of plastic products.It caters to the packaging needs of the makers of consumer goods such as catsup,to the packaging needs of the makers of plastic products.It caters to the packaging need of the makers of consumer goods such as catsup,rubbing alcohol,muriatic acid and the like.The study focused on the quality system existing in company.the quality system defined herein included the quality organization (personnel),systems and procedures,as well as the production processes.The quality system was subjected to a quality audit through the use of the Bjorklund and Sundholm Quality Function Evaluation.The quality audit covered sixteen (16) areas that were deemed vital for any quality system.The results of the audit were evaluated by the study group.From these results improvement areas were selected.The study group then proposed by the study group then proposed by the study group includes a complete listing of the personnel involved,and the instructions and procedure in their implementation.Those solutions requiring clarity in terms of purpose were also listed.Finally,the implementation program was also formulated.The details of the implementation program also included the personnel involved and the recommended.